Nutritional Status and Educational Performance of School-Aged Children in Lalibela Town Primary Schools, Northern Ethiopia - Muluken Ayalew; Alemayehu Bayray; Abate Bekele; Simegnew Handebo (Hindawi Limited, 2020)
Background. Every student has the potential to do well in school. Failing to provide good nutrition puts them at risk for missing out on meeting that potential and leads to long-term irreversible damage to cognitive development. However, taking action today to provide healthier choices in schools can help set students up for a successful future full of possibilities. So, this study is aimed at assessing the effect of nutritional status on academic performance of school-aged children. Methods. A school-based cross-sectional study was conducted from Feb 05- March 30, 2017 in Lalibela town. A total of 505 primary school students were included in the study. The child anthropometric measures were calculated using AnthroPlus software version 1.0.4 WHO 2007 standards. Bivariable and multivariable ordinal logistic regression were fitted. The proportional odds ratio (POR) with a 95% CI and P value < 0.05 were considered statistically significant. Results. The overall prevalence of stunting, underweight, and thinness was 29.5%, 35.7%, and 29.5%, respectively. In this study, 14.7% of the study participants had low academic achievement in the semester. The multivariable analysis showed that rural residence (POR=0.39; 95% CI: (0.21, 0.75)), not studying regularly (POR=0.49; 95% CI: (0.29, 0.82)), severe underweight (POR=0.25; 95% CI: (0.09, 0.71)), and severe stunting (POR=0.03; 95% CI: (0.01, 0.37)) were associated with decreased odds of high average semester score achievement of school-aged children. Additionally, higher maternal educational status (POR=2.12; 95% CI: (1.10, 4.07)) and family income from 550 to 2999 ETB (POR=1.71; 95% CI: (1.04, 2.81)) were associated with increased odds of high semester average score achievement. Conclusion. Nearly one-third of school-aged children in Lalibela town were stunted, thin, and underweight. Rural place of residence, not studying regularly study, underweight, and stunting were associated with decreased academic achievement. While, family monthly income from 550 to 2999 ETB and higher maternal education status were associated with increased academic achievement.